Structural organization of poliovirus RNA replication is mediated by viral proteins of the P2 genomic region. - Bienz, K (1990)
Transcriptionally active replication complexes bound to smooth membrane vesicles were isolated from poliovirus-infected cells. In electron microscopic, negatively stained preparations, the replication complex appeared as an irregularly shaped, oblong structure attached to several virus-induced vesicles of a rosettelike arrangement. Electron microscopic immunocytochemistry of such preparations demonstrated that the poliovirus replication complex contains the proteins coded by the P2 genomic region (P2 proteins) in a membrane-associated form. In addition, the P2 proteins are also associated with viral RNA, and they can be cross-linked to viral RNA by UV irradiation. Guanidine hydrochloride prevented the P2 proteins from becoming membrane bound but did not change their association with viral RNA. The findings allow the conclusion that the protein 2C or 2C-containing precursor(s) is responsible for the attachment of the viral RNA to the vesicular membrane and for the spatial organization of the replication complex necessary for its proper functioning in viral transcription. A model for the structure of the viral replication complex and for the function of the 2C-containing P2 protein(s) and the vesicular membranes is proposed.